2015
DOI: 10.1007/s40519-015-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

Weight management behaviors in a sample of Iranian adolescent girls

Abstract: BMI and perceived pressure from relatives, particularly mothers, and the media were important factors in attempts by adolescent girls to lose weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…In this study, their body dissatisfaction had significant difference in relation to men's. It seems that in this Iranian population, like in other studies, women are in greater risk of body dissatisfaction than men 6,11,19 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this study, their body dissatisfaction had significant difference in relation to men's. It seems that in this Iranian population, like in other studies, women are in greater risk of body dissatisfaction than men 6,11,19 .…”
Section: Discussionsupporting
confidence: 72%
“…In another study, it was shown that body dissatisfaction and the desire to be thin were common in Iranian adolescent girls 18 . Other similar studies emphasize the increase of body dissatisfaction and related issues such as weight management behaviours 19,20 .…”
Section: Introductionmentioning
confidence: 73%
“…Similar results were found in France and Spain [32,37]. However, it was lower than those observed in the United States, with 31% of males and 46% of females having followed diets to lose weight in the last year [38], in Iran, 39.7% of adolescent girls have attempted dieting to lose weight [39], and in Portugal, 39.8% of girls and 13.1% of boys reported dieting occasionally/often [40].…”
Section: Discussionsupporting
confidence: 58%
“…Out of the population with disordered eating attitudes, 16% of them present overeating, 20% purged by vomiting, and 61% food restraining [9]. These frequencies changed as people aged, with food restriction being more common in older women and vomiting during adolescence [10]. Moreover, recent data have discussed the increase of how the minimum age of the people with disorders is around 12 years of age and decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent data have discussed the increase of how the minimum age of the people with disorders is around 12 years of age and decreasing. Meanwhile, the prevalence of disordered eating attitudes appears to increase as young adults or adolescents grow older [10].…”
Section: Introductionmentioning
confidence: 99%